Atomic stacking and van-der-Waals bonding in GeTe–Sb2Te3 superlattices. Issue 20 (27th September 2016) - Momand, Jamo; Lange, Felix R.L.; Wang, Ruining; Boschker, Jos E.; Verheijen, Marcel A.; Calarco, Raffaella; Wuttig, Matthias; Kooi, Bart J.
Abstract: Abstract : GeTe–Sb2 Te3 superlattices have attracted major interest in the field of phase-change memories due to their improved properties compared with their mixed counterparts. However, their crystal structure and resistance-switching mechanism are currently not clearly understood. In this work epitaxial GeTe–Sb2 Te3 superlattices have been grown with different techniques and were thoroughly investigated to unravel the structure of their crystalline state with particular focus on atomic stacking and van-der-Waals bonding. It is found that, due to the bonding anisotropy of GeTe and Sb2 Te3, the materials intermix to form van-der-Waals heterostructures of Sb2 Te3 and stable GeSbTe. Moreover, it is found through annealing experiments that intermixing is stronger for higher temperatures. The resulting ground state structure contradicts the dominant ab-initio results in the literature, requiring revisions of the proposed switching mechanisms. Overall, these findings shed light on the bonding nature of GeTe–Sb2 Te3 superlattices and open a way to the understanding of their functionality.